2016
DOI: 10.5713/ajas.16.0499
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat preference and effects on performance of piglets at weaning

Abstract: ObjectiveAn experiment was to evaluate the interplay of dietary lipid sources and feeding regime in the transition from sow milk to solid food of abruptly weaned piglets.MethodsSoon after weaning, 144 piglets were selected and were trained over a 15 day period to experience gradually reducing dietary fat content from 12% to 6% for lard (L), soybean oil (S), and coconut oil (C) and their feeding behavior and diet preference then tested in a behavior observation experiment. Another 324 weaned piglets were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…This is possibly due to increased oxidative stress resulting from SO as compared to AF high in saturated fatty acids. Similar results of better performance of young pigs were observed when pigs were fed diets containing lard than when they were fed diets containing SO [29]. However, there was no additional benefit of increasing inclusion levels from 2.0% to 4.0% of both AF and SO on productive performance of laying hens raised under hot environmental conditions.…”
Section: Discussionsupporting
confidence: 66%
“…This is possibly due to increased oxidative stress resulting from SO as compared to AF high in saturated fatty acids. Similar results of better performance of young pigs were observed when pigs were fed diets containing lard than when they were fed diets containing SO [29]. However, there was no additional benefit of increasing inclusion levels from 2.0% to 4.0% of both AF and SO on productive performance of laying hens raised under hot environmental conditions.…”
Section: Discussionsupporting
confidence: 66%
“…Other authors, however, have described improvements in performance related to the supplementation of MCFA. Some works evaluating MCFA as an energy source, at higher doses (2.1–7.75%), registered growth improvements [6, 13, 46, 47] that could be justified by the more rapid digestion and absorption of these fatty acids. Improvements have also been seen in animals challenged with ETEC F4 or LPS [23, 48], however, not necessarily by using high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Several published works can be found substituting fat sources with purified MCFA or alternative natural sources rich in MCFA, leading to improvements in the performance of piglets around weaning [12, 13]. Studies with healthy pigs [1416] have demonstrated positive effects on growth performance, digestibility, and intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In modern pig production, weaning is still associated with nutritional, environmental and immune challenges that may lead to considerable economic losses to pork producers (Li et al, 2014;Weng, 2017). Generally, weaning period is characterized by decreased feed intake, altered gut integrity and increased concentrations of inflammatory markers in blood (Le Dividich and Sève, 2000;Pié et al, 2004;Montagne et al, 2007).…”
Section: Introductionmentioning
confidence: 99%